Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai Pada Badan Keuangan dan Aset Daerah Kabupaten Maros - Mutia Ramadani; Akmal Umar; Adrianah (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2025)
This research aims to find out the influence of work discipline and work motivation on employee performance at the Regional Financial and Asset Agency of Maros Regency. A total of 92 respondents were used as the research population and sample. Data collection techniques in this research include observation, interviews, questionnaires and documentation. The data analysis techniques were validity and reliability testing, normality testing, hypothesis testing, regression testing (T test and F test) with SPSS V 26. The results of this research show ed, partially, the variable of work discipline variables has a positive and significant effect on employee performance. In employee performance, work motivation has a positive and significant effect. Simultaneously work discipline and work motivation has a significant effect on employee performance. The R square value was 0.257 or 25.7%, which means work discipline and work motivation are 25.7% and the remaining 74.3% is influenced by other variables that are not used in this research.